Different Paths, Different Summits: A Model for Religious Pluralism - Kaplan, Stephen (Rowman & Littlefield Publishers, 2001)
In a world where religious pluralism is a necessity of modern life, diverse religions exist for the diverse people populating the earth. Theologically, how do people of different faiths find liberation in their separate gods simultaneously? Stephen Kaplan answers this question with his new book, Different Paths, Different Summits. He presents a model for religious pluralism that does not fall victim to the criticisms of pluralist models. Religious positions do not need to be transcended in order for varying faiths to be both honored and liberating simultaneously. Kaplan skillfully depicts three different realties, a theistic ultimate reality, a monistic ultimate reality, and a process non-dualism, along with their beliefs. His model allows for each to exit simultaneously, mutually interpenetrating and distinct.